The John Zink-Hamworthy combustion handbook. Volume 2, - Baukal, Charles E., Jr., 1959- (Industrial combustion series., 2013)
Despite the length of time it has been around, its importance, and vast amounts of research, combustion is still far from being completely understood. Issues regarding the environment, cost, and fuel consumption add further complexity, particularly in the process and power generation industries. Dedicated to advancing the art and science of industrial combustion, The John Zink Hamworthy Combustion Handbook, Second Edition: Volume 2 - Design and Operations serves as a field manual for operators, engineers, and managers working in design and operations. Under the leadership of Charles E. Baukal,